The 4th European Society for Medical Oncology Asia Congress: bridging ultimate cancer care with real-world practice for the Asian practitioner in gynecological cancers - Ngoi, Natalie YL (KOREAN SOC GYNECOLOGY ONCOLOGY & COLPOSCOPY, 2021)
10.3802/jgo.2019.30.e48